A Language Stimulation Analysis of Cantonese-English Bilingual Infants in Hong Kong. (November 2013) - Yip, Michael C. W.
This study measured naturalistic language stimulation in Hong Kong among eight bilingual (Cantonese, English) infants. Two findings were that (a) infants received more indirect (adult-to-adult) than direct (adult-to-infant) language stimulation and (b) infants received 6.8 hr of language stimulation per day with more fillers, vocatives, and baby talk than declaratives, interrogatives, and imperatives.